2022
DOI: 10.1038/s41467-022-34847-9
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional hyperspin machine

Abstract: From condensed matter to quantum chromodynamics, multidimensional spins are a fundamental paradigm, with a pivotal role in combinatorial optimization and machine learning. Machines formed by coupled parametric oscillators can simulate spin models, but only for Ising or low-dimensional spins. Currently, machines implementing arbitrary dimensions remain a challenge. Here, we introduce and validate a hyperspin machine to simulate multidimensional continuous spin models. We realize high-dimensional spins by pumpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…As a result, they express two possible solutions for input power levels higher than 𝑃 𝑡ℎ : one stable and one unstable. These solutions are phase-shifted by 𝜋 with respect to each other and, in the absence of noise, can be reached equiprobably 32 (see Supplementary Section II). When two POs are coupled by an impedance 𝑍 𝐶 in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result, they express two possible solutions for input power levels higher than 𝑃 𝑡ℎ : one stable and one unstable. These solutions are phase-shifted by 𝜋 with respect to each other and, in the absence of noise, can be reached equiprobably 32 (see Supplementary Section II). When two POs are coupled by an impedance 𝑍 𝐶 in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the realm of optimization, the Ising model has been employed to describe the collective behavior of dissipatively coupled parametric oscillators (POs) [27][28][29][30][31] . Within this framework, studies have revealed that a network of resistively coupled electrical POs naturally converges towards a collective oscillation state that minimizes a Lyapunov function 32,33 . This allows the network to evolve towards the ground state configuration of its Hamiltonian, enabling the use of networks of POs to solve combinatorial optimization problems 27,29,[32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is interesting to note that these algorithms thus seem to keep a set of optimization parameters (the 𝐽𝐽 𝑖𝑖𝑖𝑖 matrix) fixed while interpolating between two distinct domains for the optimization variables -starting with real values allowed but ending with a restriction to binary values. Recently, more general domain interpolations 7,8 have been investigated for CIM variants.…”
Section: Introductionmentioning
confidence: 99%